Framing and argumentative markers in narratives of Dutch learners of French as a second language. Preliminary results of a corpus study. - Welcomme, Aurélie; Pierrard, Michel (Círculo de Lingüística Aplicada a la Comunicación, 2013)
This article discusses the presence and frequency of use of framing and argumentative markers in narratives of Dutch learners of French in Brussels and Flanders. These learners are either at the beginning (1st year) or end (6th year) of their secondary school education. First, we provide with an overview of the notions that are analysed in the corpus. Next we describe the corpus and the task used, and then continue with a discussion of the results of the quantitative and qualitative analyses. To conclude, we sum up the main findings of our study.
Keywords: acquisition of French as a foreign language; framing markers; argumentative markers